Successful DC current limitation above 100 Vm−1 for 50 ms using HTS tapes with critical currents exceeding 750 A/cm-width. (13th January 2021) - Lacroix, Christian; Lavergne, Olivier; Leduc, Thomas; Dupuis-Desloges, Félix; Moret, Lucile; Sirois, Frédéric; Escamez, Guillaume; Bruzek, Christian-Éric; Tixador, Pascal; Grosse, Veit; Bauer, Markus
Abstract: High-voltage direct current transmission systems are expected to allow the transmission of huge volumes of electricity over long distances. The use of superconducting fault current limiters (SFCLs) based on second-generation (2G) high-temperature superconductor (HTS) coated conductors (CCs) is a promising solution to mitigate fault currents in DC transmission systems. To fabricate a SFCL whose size remains acceptable, which means minimizing the length of the HTS tape used, the tape must sustain a high electric field during the whole fault duration. In this paper, high performance commercial 2G HTS CCs from THEVA (more than 750 A/cm-width at 77 K in self-field), on which a 500 µ m thick Hastelloy shunt was soldered, were tested by submitting them to faults of different amplitudes and durations. Measurements revealed that these HTS tapes could sustain any type of fault up to 100 V m −1, lasting up to 50 ms. Three-dimensions finite element simulations were able to reproduce accurately the experiments by using the appropriate temperature dependence of the critical current density and power law index, and by accounting for the variations in the local critical current along the length of the HTS tapes.